PERAN KONSELING INDIVIDU DENGAN PENDEKATAN COGNITIVE BEHAVIOR THERAPY (CBT) UNTUK MENGATASI KORBAN BODY SHAMING KELAS IX SMP NEGERI 7 KOTA SURAKARTA TAHUN PELAJARAN 2025/2026 - Risma Yoga Noviana; Heru Sri Suryanti, Hera; Adi Putro, Eko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The aim of this research is to determine the role of individual counseling services with the Cognitive Behavior Therapy (CBT) approach in addressing the impacts of body shaming on ninth-grade students of SMP Negeri 7 Surakarta City in the Academic Year 2025/2026. This research is a Guidance and Counseling Action Research (PTBK) conducted in 3 cycles. The data collection techniques used were observation, interviews, and Likert scale. This research was conducted at SMP Negeri 7 Surakarta City. The subject of this research was one student with the initials TKIEIP. CBT approach through cognitive restructuring techniques was able to address the impacts of body shaming on students. In cycle I, the results showed a reduction in the impacts of body shaming with an observation percentage of 63.40% and a scale percentage of 61.05%, although there were still some indicators that had not been resolved. In cycle II, the reduction results improved with an observation percentage of 42.60% and a scale percentage of 40.20%, but there were still indicators that had not been resolved, so it continued to cycle III. In cycle III, subject TKIEIP achieved the target set by the researcher with an observation percentage of 30.60% and a scale percentage of 28.40%, reaching the very low category.